Investigation of the effect of chitin nanowhiskers distribution on structural and physical properties of high impact polypropylene/chitin nanocomposites - Nel, Alicia (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2014.